2017
DOI: 10.4253/wjge.v9.i2.70
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for small submucosal tumors of the rectum compared with endoscopic submucosal resection with a ligation device

Abstract: AIMTo evaluate the efficacy and safety of endoscopic submucosal dissection (ESD) for small rectal submucosal tumors (SMTs).METHODSBetween August 2008 and March 2016, 39 patients were treated with endoscopic submucosal resection with a ligation device (ESMR-L) (n = 21) or ESD (n = 18) for small rectal SMTs in this study. Twenty-five lesions were confirmed by histological evaluation of endoscopic biopsy prior to the procedure, and 14 lesions were not evaluated by endoscopic biopsy. The results for the ESMR-L gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
2
16
1
Order By: Relevance
“…Carcinoid tumors, derived from neuroendocrine cells compartments, mostly arise along the intestine, among which rectum was found to be the third most frequent predilection site 1 , 2 . Currently, rectal carcinoids with adverse features for metastasis including diameters larger than 20mm, invading muscularis propria, lymphovascular invasion or positive regional lymph node, are suggested to be removed by radical surgery, while tumors in diameters 10mm or less are supposed to be treated by local resection 3 - 5 . As for the carcinoids sized between 10mm to 20mm, the management remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Carcinoid tumors, derived from neuroendocrine cells compartments, mostly arise along the intestine, among which rectum was found to be the third most frequent predilection site 1 , 2 . Currently, rectal carcinoids with adverse features for metastasis including diameters larger than 20mm, invading muscularis propria, lymphovascular invasion or positive regional lymph node, are suggested to be removed by radical surgery, while tumors in diameters 10mm or less are supposed to be treated by local resection 3 - 5 . As for the carcinoids sized between 10mm to 20mm, the management remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically complete resection rates of 28.6 % to 100 % have been reported for conventional polypectomy or EMR for rectal NET G1 2 . In addition, some studies reported R0 resection rates as high as 82.8 % to 100 % with ESMR-L 2 8 9 , and 80.6 % to 100 % with ESD 3 8 9 . However, 1 of the main reasons for the difficulties encountered during endoscopic resection of NET G1 is that most of them extend to the submucosa 1 , necessitating resection of the submucosal layer under the NET.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In the context of large colon lipomas, several endoscopic techniques have been reported, such as loop-assisted techniques and snare resection. However, in situations where the dimensions of the lesion make these methods unfeasible, endoscopic submucosal dissection (ESD), 3,4 other dissection-based techniques and, most importantly, simple unroofing may offer effective alternative treatment options. [5][6][7][8][9][10] Mentioned for the first time in 1997, the unroofing technique relies on intraluminal expulsion of the residual submucosal content following snare resection of the distal part of the subepithelial mass 11 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of large colon lipomas, several endoscopic techniques have been reported, such as loop‐assisted techniques and snare resection. However, in situations where the dimensions of the lesion make these methods unfeasible, endoscopic submucosal dissection (ESD), 3,4 other dissection‐based techniques and, most importantly, simple unroofing may offer effective alternative treatment options 5–10 …”
Section: Introductionmentioning
confidence: 99%